2011
DOI: 10.1637/9813-052511-case.1
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Body Hepatitis Caused by Fowl Adenovirus in Broiler Chickens in Japan, 2009–2010

Abstract: From January 2009 to June 2010, many broiler chicks suddenly died without clinical signs. The mortality rates were from 1.2% to 17.0% in affected flocks. Inclusion body hepatitis (IBH) was detected in 13 prefectures (northern, eastern, western, and southern areas) in Japan. The livers were enlarged and pale. The bursa of Fabricius and thymus had not atrophied. Multifocal necroses of hepatocytes with basophilic intranuclear inclusions were seen in the liver. Eosinophilic intranuclear inclusion bodies in hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
34
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 18 publications
7
34
1
1
Order By: Relevance
“…Experimental infection of chickens with certain FAdV strains has demonstrated disease and mortality due to FAdV alone (Erny, Barr, & Fahey, 1991;Mazaheri, Prusas, Voss, & Hess, 1998;Saifuddin & Wilks, 1992). FAdV has also been found to be primarily responsible for field cases of severe clinical disease, where other viral agents were not found to be present (Gomis, Goodhope, Ojkic, & Willson, 2006;Nakamura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental infection of chickens with certain FAdV strains has demonstrated disease and mortality due to FAdV alone (Erny, Barr, & Fahey, 1991;Mazaheri, Prusas, Voss, & Hess, 1998;Saifuddin & Wilks, 1992). FAdV has also been found to be primarily responsible for field cases of severe clinical disease, where other viral agents were not found to be present (Gomis, Goodhope, Ojkic, & Willson, 2006;Nakamura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, earlier reports about IBH in New Zealand had already indicated that IBH can be a primary disease which was confirmed in a series of more recent reports of IBH outbreaks in Canada, Australia and Japan (Christensen and Saifuddin, 1989; Gomis et al ., 2006; Nakamura et al ., 2011; Steer et al ., 2011). In addition, the prevalence of FAdV does not coincide with the presence of IBDV or CAV (Eregae et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A larger number of IBH outbreaks were reported from Canada (Pettit and Carlson, 1972) and Iraq (Al-Sheikhly and Mutalib, 1979) based on histological diagnosis until the disease was reported from New Zealand (Saifuddin et al ., 1992) and Australia (Erny et al ., 1991), predominantly caused by FAdV-8. Single case reports were published until about 10 years ago when the number of outbreaks in geographically different areas worldwide increased substantially (Gomis et al ., 2006; Ojkic et al ., 2008 a , 2008 b ; Lim et al ., 2011; Nakamura et al ., 2011; Steer et al ., 2011; Choi et al ., 2012; Kaján et al ., 2013; Maartens et al ., 2015; Zhao et al ., 2015; Niczyporuk, 2016; Schachner et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, IBH outbreaks have been detected in different countries; serotypes 2, 4, 8a, 8b and 11 have been the most frequent serotypes involved (Grgic et al, 2011;Nakamura et al, 2011;Steer et al, 2011;Choi et al, 2012;Dar et al, 2012;Kajan et al, 2013;Joubert et al, 2014;Zhao et al, 2015;Schachner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%